Macroeconomic impact of Covid-19 on business in Morocco : Assessment and recommendations - BACHISSE , Mohamed; MOULINE , Boubker (Revue Internationale du Chercheur, 2021)
The crisis linked to the spread of Covid-19 has had a considerable impact on the global economy. Indeed, this health crisis quickly turned into a real economic crisis, thus calling on governments to be vigilant but also to flexibility in order to adapt to this unstable context. In Morocco, the state mobilized by proposing various measures from the start of the crisis health in order to minimize the impact of this pandemic and preserve the social stability of a side and the maintenance of stable economic activity on the other. While, these measures might be effective in mitigating the effects of the pandemic on the short term; it seems that the economic toll might be higher than expected in the medium and long term. Even more, the government response regarding economic recovery has been characterized by a wait and see attitude. It is still too early to clearly measure the impact of this pandemic on the moroccan economy. Nevertheless, this paper will present the immediate consequences of this crisis on the macroeconomic side and economic growth. It also proposes some strategic areas where the government can intervene in order to contain the economic impact of the pandemic on the medium to long term.